Input of plastic debris in an urban tropical river system. (July 2019) - Bauer-Civiello, Anne; Critchell, Kay; Hoogenboom, Mia; Hamann, Mark
Abstract: Land-based sources contribute approximately 80% of anthropogenic debris in marine environments. A main pathway is believed to be rivers and storm-water systems, yet this input is rarely quantified. We aimed to quantify the abundance of land-based debris entering a river system through storm drains in an urban area of tropical Australia. To account for seasonal variability, debris was quantified pre, post and during the wet season from 2014 to 2017. Plastic items within the river were compared to those in adjacent parks to assess similarities in debris composition. A total of 27, 943 items were collected (92% plastic). Debris loads in the post-wet seasons were significantly higher than the wet-season. Furthermore, variability in the portion of debris found in nearby parks compared to the river suggests that factors other than rainfall, play a role in debris abundance. These results can be used to identify targeted management strategies to reduce debris loads. Highlights: A total of 27, 943 anthropogenic debris items were collected from a Queensland river over four consecutive years. There was a consistent input of debris in the river through time, even in years of low rainfall. The abundance of debris collected during the wet season was unexpectedly lower than that collected in the post-wet seasons. Debris in different sections of the river appeared to be from different sources depending on the site location.